Familial Traces: Photography and Trauma in Doris Lessing’s Auto/biographical Narratives - Arias-Doblas, María Rosario (My University, 2014)
This paper deals with the use of photography in Doris Lessing’s auto/biographical writings, particularly, Under My Skin: Volume One of My Autobiography, to 1949 (1994), and more recently, Alfred and Emily (2008). Both works deal with Lessing’s personal and collective trauma: her strained relationship with her mother, and her struggle for recognition, as well as the pernicious influence the Great War had upon Lessing’s parents, and by extension, upon Lessing herself. Trauma studies, as seen in the winter-spring 2008 special double issue of Doris Lessing Studies entirely devoted to trauma in Lessing’s work, have provided nuanced readings into Lessing’s take on trauma in her production. Although the (im)possibility of recovery from trauma has become a recent focus of interest in Lessing studies, as in the double issue, there has been no specific reference to the relevance of photography and/in trauma. The aim of this paper is to examine personal photographs as relevant cultural documents in Lessing’s auto/biographical texts, and her engagement with personal and collective trauma, by paying attention to a neglected aspect: the use of family photography.
Keywords: Lessing, Doris May - Crítica e interpretación; Doris Lessing; Photography; Trauma; Autobiography